Desigualdades digitais, políticas e sociais no Brasil : um diálogo entre as abordagens do comportamento político e dos estudos de internet - Jaqueline Resmini Hansen (2021)
This research aims to describe and explore the relationship between digital, political and social inequalities through the analysis of the Brazilian case. Starts from the notion of social inequalities as categorical inequalities of social position that lead to the reproduction of advantages in other categories, such as digital and political. This framework allows us to focus on the connection between digital and political inequalities and to explore their relationship. From the political behavioral field, the Civic Volunteerism Model is mobilized to define political inequalities as differences in political participation, and to maintain that they suffer a determination of social inequalities. To bring digital inequalities into debate, the online environment is framed within the dimension of opportunities as a space centered on writing and communication among many. Thus, from the field of internet studies, Theory of Resources and Appropriations is mobilized to define that digital inequalities are expressed at three levels and are determined by social inequalities. The Corresponding Fields Model is used to argue that online environment provides a field corresponding to the spaces of offline opportunities, that enable the development of useful skills for political participation. Finally, the socio-technical studies approach is mobilized to show that architecture of web platforms acts in relation to categorical inequalities through technical constraints, capable of perpetuating individuals in advantageous positions in society. These theoretical approaches support a descriptive research design that explores the relationship between digital and political inequalities, considering the inclusion of the internet as the first level of digital inequalities and the skills and uses of the online environment as the second level. The first relation is described through a dependency key through a Moderation Analysis through Logistic Regression. The second is explored in a key of interdependence and a Multiple Correspondence Analysis was used to describe the distinction between groups. This analyzes indicated that relations between categorical inequalities have a tendency to amplify and reproduce social inequalities. Therefore, the main contribution that the description of relations between categorical inequalities shows is that although the online environment has a civic potential to provide experiences that exercise skills necessary for political participation, this system of opportunities is constrained by social and technical aspects that act to support the process of reproducing advantageous positions